IMPLEMENTASI PERMENDIKNAS NOMOR 28 TAHUN 2010 TENTANG PENUGASAN GURU SEBAGAI KEPALA SEKOLAH DI KABUPATEN SIAK - Fauziah Fauziah; Jimmi Copriady; Sudirman Sudirman (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2021)
Permendiknas implementation research on the appointment of pricipals is inseparable from the basic permendiknas namely: (1) permendiknas number 13 year 2007 about pricipal standar, (2) permendiknas number 28 tahun 2010 about teacher assignment as Head of school. This research discloses how the process of appointment of headmaster of SMP negeri in Dinas Education and culture of  Siak Regency, is in accordance with the provisions set by the government in permendiknas number 28 year 2010. This implementation research isbased on metter and Horn theory and describe the findings using approach qualitative methods. Data obtained by interviuw, observation and document. Futher data are analyzed and performed continuously to complate. The results of the study note that the general requirements in administrative selection are not met well. Because three is still the age of principals who do not meet the provisions with the number 85%. This means that only 15% of the principals are appointed in accordance with the provisions of the first appointment process in office. Even 29% of headmaster who served in Siak district will now undergo more than 2 periods of duty. At the rank and class of principals also found 13% of principals who are currently still in rank/class IIIB. While on special requirenments found arround 65% of  school principas in Siak Regency do not have a certificate of principal issued by LP2KS is a NUKS certificate. There are several factors that become obstacles in implementing permendiknas number 28 year 2010 in Siak Regency. Namale; (1) the SDK of siak Distric employees, especially the lack of education, (2) the cost of education and training to obtain NUKS certificate, (3) the role of the acceptability team in the process of placing the principal the carry out his duties as principal.